2011
DOI: 10.1111/j.1439-0264.2011.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Mineral Apposition Rate in distal femoral epiphysis of New Zealand White Rabbit at Skeletal Maturity

Abstract: Studies investigating the effect of different factors on the skeletal system require characterization of an appropriate animal model. Rabbits are among the most commonly studied animals for medical research, being used in about 35% of musculoskeletal research studies. The present dynamic cross-sectional histomorphometric study quantitatively determined mineral apposition rates (MARs) in the distal femoral epiphysis in four regions of interest (ROIs) in New Zealand white rabbits. ROIs included the craniolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Thus, bone forms at an approximately constant rate r B = d(%B)/dt = mineral apposition rate, which has been reported as *4 mm$day -1 for the distal femur of rabbits. 36 However, b = 0.307 in the inner region of group BC (Fig. 7B), indicating that the rate of new bone formation decreased from 6 to 12 weeks.…”
Section: Histology and Histomorphometrymentioning
confidence: 89%
“…Thus, bone forms at an approximately constant rate r B = d(%B)/dt = mineral apposition rate, which has been reported as *4 mm$day -1 for the distal femur of rabbits. 36 However, b = 0.307 in the inner region of group BC (Fig. 7B), indicating that the rate of new bone formation decreased from 6 to 12 weeks.…”
Section: Histology and Histomorphometrymentioning
confidence: 89%
“…12 A previous study aimed at evaluating the MAR in a single cross-section plane within the femur reported differences among the ROIs during the experimental times considered. 27 Although different ROIs within each skeletal element were selected in this study, we did not focus on the changes in the MAR within these regions as the influences of muscle and tendon insertions were not analysed.…”
Section: Discussionmentioning
confidence: 99%
“…4). This ROI comprises epiphyseal bone, which is a preferred region for trabecular analyses in skeletally mature New Zealand White rabbits based on more robust trabecular architecture compared with the trabecular-poor metaphyseal region [21]. The trabecular ROI for L4 begins at a point that is 1/8th of the vertebral body’s height superior to the caudal end-plate and extends proximally 2 mm (133 slices) (Fig.…”
Section: Methodsmentioning
confidence: 99%